Novel material for adsorbing cadmium and lead heavy metals as well as preparation method and application of novel material
A novel adsorbent material was prepared by heating and roasting low-grade oil shale, which solved the problems of high energy consumption and complex adsorbent preparation in existing heavy metal wastewater treatment methods, and achieved efficient adsorption of cadmium and lead heavy metals and environmentally friendly and economical wastewater treatment.
Patent Information
- Application Number
- CN202511417903.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2025-11-25
AI Technical Summary
Existing methods for treating heavy metal wastewater suffer from high energy consumption, poor effluent quality, and poor treatment effect on low-concentration heavy metal wastewater. Furthermore, common adsorbent preparation processes are complex, and the raw materials are not environmentally friendly enough.
Using low-grade oil shale as raw material, a novel adsorbent material was prepared by heating and roasting to change its surface properties, increase its specific surface area and chemical bond activity, and then used to adsorb heavy metals such as cadmium and lead.
The newly prepared adsorbent material exhibits rapid, significant, and stable adsorption effects on heavy metals such as cadmium and lead. The raw materials are economical and environmentally friendly, and the preparation process is simple, making it suitable for practical production remediation and treatment.
Smart Images

Figure CN121003969A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment technology, specifically to a novel material for adsorbing heavy metals such as cadmium and lead, its preparation method, and its application. Background Technology
[0002] In recent years, with the rapid advancement of modernization and the booming development of industry, a large amount of industrial, agricultural, and domestic wastewater, waste gas, and waste residue have been generated. These "three wastes" ultimately enter water bodies to varying degrees, polluting various water bodies. Currently, the global water environment suffers from varying degrees of heavy metal pollution, particularly cadmium and lead. Due to their long-lasting nature, high hazard, and difficulty in treatment, these pollutants easily enter the human body through the food chain, posing a serious threat to human health. Heavy metal wastewater treatment methods include chemical precipitation, oxidation-reduction, ion exchange, and adsorption. Given the complexity of heavy metal pollution in water bodies, to reduce its harm to the environment and organisms, it is necessary to select safer and more efficient treatment methods based on the actual pollution situation to solve the problem of heavy metal pollution in water bodies. Although the treatment methods for heavy metal wastewater have made significant progress, the commonly used methods still have drawbacks such as high energy consumption, poor effluent quality, and poor treatment effect on low-concentration heavy metal wastewater.
[0003] Adsorption is widely used in the treatment of heavy metal pollution in water bodies due to its simplicity and high efficiency. The selection of adsorbents is crucial for meeting the requirements of pilot-scale and industrial-scale production. A good heavy metal adsorbent typically needs to possess high adsorption capacity, rapid adsorption of heavy metals, adjustable adsorption and desorption processes, easy recycling and regeneration, long-term reusability, low cost, and environmentally friendly raw materials and finished products. Common adsorbents include activated carbon, mineral adsorbents, and organic polymers. However, the preparation processes of most adsorbents are complex, and their raw materials and adsorbents are not sufficiently environmentally friendly. Therefore, the search for adsorbents with simple processes and low energy consumption throughout the entire process is a key research focus.
[0004] Oil shale, a fine-grained sedimentary rock with fine bedding and rich in combustible organic matter, contains a large amount of amphoteric oxides. Its development generates a large amount of ash byproducts, mainly of two types: solid waste from shale oil extraction and low-grade oil shale containing oil but with low yield. Both types of solid waste have high SiO2 and Al2O3 contents, possessing potential as adsorbent materials. The comprehensive utilization of low-grade oil shale is particularly advantageous due to its low cost, recycling, and waste-to-resource conversion. For example, CN 110523373 B provides a method for preparing oil shale semi-coke adsorbents, mainly by mixing oil shale semi-coke with biomass agricultural and forestry waste to prepare highly active adsorbents. However, the preparation process is complex, requiring the addition of activators (NaOH, KOH, ZnCl2, or phosphoric acid) and acid washing with dilute hydrochloric acid, sulfuric acid, phosphoric acid, or nitric acid at a concentration of 0.5–1 mol / L, resulting in a significant amount of additional reagents. Summary of the Invention
[0005] The purpose of this invention is to provide a novel material for adsorbing heavy metals such as cadmium and lead, as well as its preparation method and application, in order to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a novel material for adsorbing heavy metals such as cadmium and lead, the method comprising:
[0007] The low-grade oil shale was ground through a 200-mesh sieve and dried to a constant weight.
[0008] The dried oil shale is placed in a tubular rotary furnace, nitrogen is introduced and air is purged to maintain the furnace pressure at 0.2 atmospheres; it is heated to 200℃-800℃ at a constant heating rate and calcined at this temperature for 2 hours.
[0009] The calcined oil shale was cooled to room temperature, then ground and sieved again to obtain a new type of adsorbent material.
[0010] As a further embodiment of the present invention, the drying temperature of the low-grade oil shale is 45℃-55℃.
[0011] As a further embodiment of the present invention, the drying temperature of the low-grade oil shale is 50°C.
[0012] As a further embodiment of the present invention, the heating rate is 3-7°C / min.
[0013] As a further embodiment of the present invention, the heating rate is 5°C / min.
[0014] As a further embodiment of the present invention, the heating temperature is 600°C.
[0015] This invention also provides a novel material prepared by the aforementioned method, which is effective against Cd in wastewater. 2 The suitable adsorption concentration for Pb is <100 mg / L. 2 The suitable adsorption concentration for + is <300mg / L.
[0016] This invention also provides the application of a novel material in the adsorption of cadmium and lead heavy metals in wastewater.
[0017] Compared with the prior art, the beneficial effects of the present invention are: by heating and roasting, the surface properties of oil shale are changed, the specific surface area of oil shale is increased, the activity of some chemical bonds is enhanced, and the adsorption capacity is improved. It can be used for the adsorption of cadmium and lead in wastewater, and the adsorption effect is rapid, significant, stable and efficient.
[0018] The raw material is low-grade oil shale, which is a large amount of ash and slag generated during the development of oil shale. It is green, economical, and inexpensive. Moreover, the preparation method of this invention is simple, highly operable, and easy to apply to actual production, remediation and treatment. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention.
[0020] Figure 1 These are SEM images of Examples 1, 2, and the control group of the present invention.
[0021] Figure 2 These are SEM images of Embodiments 3 and 4 of the present invention.
[0022] Figure 3 This is an XRD diagram of an embodiment of the present invention.
[0023] Figure 4 This is an FTIR diagram from an embodiment of the present invention.
[0024] Figure 5 The effects of different temperatures on Cd in oil shale semi-coke materials prepared according to embodiments of the present invention. 2+ Pb 2+ Line graph of adsorption capacity versus removal rate.
[0025] Figure 6 This invention provides examples of the effects of different adsorption times on Cd in oil shale samples and semi-coke materials. 2+ Pb 2+ The adsorption amount is shown in the line graph.
[0026] Figure 7 Example 3 and the control group of the present invention are for the effect of Cd 2+The adsorption situation.
[0027] Figure 8 Example 3 and the control group of the present invention are for Pb 2+ Adsorption situation Detailed Implementation
[0028] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0029] Example 1: A method for preparing a novel material for adsorbing heavy metals such as cadmium and lead, the method comprising:
[0030] A suitable amount of low-grade oil shale was ground through a 200-mesh standard inspection sieve and dried to constant weight at 45°C in an electric heating constant temperature oven. The dried oil shale was then placed in a tubular rotary kiln (model: ZYC0-60*300, manufactured by Dongguan Zhiyuan Semiconductor Co., Ltd.). Nitrogen was introduced to purge the air from the tubes, and then the valve was closed. Once the pressure in the rotary kiln reached 0.2 atmospheres, nitrogen filling was stopped, indicating that the anaerobic standard had been met.
[0031] The oil shale semi-coke material was prepared by heating to 200℃ at a heating rate of 3℃ / min and calcining at this temperature for 2 hours. It is denoted as OS-200.
[0032] After the calcined oil shale is cooled to room temperature, it is ground again and passed through a 200-mesh standard inspection sieve before being packaged and stored for later use.
[0033] Example 2: A method for preparing a novel material for adsorbing heavy metals cadmium and lead, the method comprising:
[0034] Grind an appropriate amount of low-grade oil shale through a 200-mesh standard test sieve and dry it at 55°C in an electric heating constant temperature box until it reaches a constant weight. Place the dried oil shale in a tubular rotary kiln, fill it with nitrogen to purge the air from the tube, then close the valve. After the gas pressure in the rotary kiln reaches 0.2 atmospheres, stop the nitrogen filling and determine that the anaerobic standard has been met.
[0035] The oil shale semi-coke material was prepared by heating to 400℃ at a heating rate of 7℃ / min and calcining at this temperature for 2 hours. It is denoted as OS-400.
[0036] After the calcined oil shale is cooled to room temperature, it is ground again and passed through a 200-mesh standard inspection sieve before being packaged and stored for later use.
[0037] Example 3: A method for preparing a novel material for adsorbing heavy metals cadmium and lead, the method comprising:
[0038] Grind an appropriate amount of low-grade oil shale through a 200-mesh standard test sieve and dry it at 50°C in an electric heating constant temperature oven until it reaches a constant weight. Place the dried oil shale in a tubular rotary furnace, fill it with nitrogen to purge the air from the tube, then close the valve. After the gas pressure in the rotary furnace reaches 0.2 atmospheres, stop the nitrogen filling and determine that the anaerobic standard has been met.
[0039] The oil shale semi-coke material was prepared by heating to 600℃ at a heating rate of 5℃ / min and calcining at this temperature for 2 hours. It is denoted as OS-600.
[0040] After the calcined oil shale is cooled to room temperature, it is ground again and passed through a 200-mesh standard inspection sieve before being packaged and stored for later use.
[0041] Example 4: A method for preparing a novel material for adsorbing heavy metals cadmium and lead, the method comprising:
[0042] Grind an appropriate amount of low-grade oil shale through a 200-mesh standard test sieve and dry it at 50°C in an electric heating constant temperature oven until it reaches a constant weight. Place the dried oil shale in a tubular rotary furnace, fill it with nitrogen to purge the air from the tube, then close the valve. After the gas pressure in the rotary furnace reaches 0.2 atmospheres, stop the nitrogen filling and determine that the anaerobic standard has been met.
[0043] The oil shale semi-coke material was prepared by heating to 800℃ at a heating rate of 5℃ / min and calcining at this temperature for 2 hours. It is denoted as OS-800.
[0044] After the calcined oil shale is cooled to room temperature, it is ground again and passed through a 200-mesh standard inspection sieve before being packaged and stored for later use.
[0045] In the control group, an appropriate amount of low-grade oil shale was ground through a 200-mesh standard test sieve and dried to constant weight at 50°C in an electric heating constant temperature oven. The resulting dried low-grade oil shale was denoted as OS-Y.
[0046] The oil shale semi-coke materials prepared in each embodiment can be characterized and observed using the following methods:
[0047] like Figure 1 and Figure 2As shown, microscopic characterization was performed using SEM to obtain the surface features of oil shale before and after semi-coking. The surface of uncoked OS-y was relatively dense and smooth, with irregularly distributed fine particles and no significant porous structure. After semi-coking at 200℃, the surface structure collapsed, exhibiting a layered structure. This process altered the surface roughness of the oil shale, increasing the surface area and enhancing its adsorption capacity for heavy metals. Between 200 and 600℃, as the coking temperature increased, the platy structure continued to develop, further collapsing the surface structure and highlighting the layered structure. Under the driving force of sintering, the platy grains merged, increasing their structural size until the platy structure gradually decreased. When the temperature reached 800℃, granular structures began to appear internally. Oil shale is rich in organic matter. During the semi-coking process, the C content decreased from 57.6% in OS-y to 33.6% in OS-800, while the corresponding Si and Al contents increased. In OS-600, the Si and Al contents increased to 16.0% and 8.3%, respectively, which are 3.32 times and 1.86 times higher than those in OS-y. During this process, substances such as CO2 and shale oil were precipitated on the surface, altering its surface structure.
[0048] like Figure 3 As shown, the chemical composition and XRD analysis are as follows: The XRD patterns of oil shale before and after semi-coking show that the mineral composition of oil shale is basically the same before and after semi-coking, mainly including quartz (SiO2), kaolinite (Al2Si2O5(OH)4) and pyrite (FeS2). During the process of increasing the semi-coking temperature from 200℃ to 800℃, the mineral crystal structure in oil shale did not change drastically. The characteristic diffraction peaks of SiO2, Al2Si2O5(OH)4 and FeS2 did not disappear or change significantly, indicating that the preparation method basically did not change the mineral composition of natural oil shale.
[0049] Specific surface area analysis: As shown in the table below, the specific surface area of oil shale after semi-coking increases significantly. The specific surface area of semi-coking oil shale produced at different coking temperatures varies considerably, with OS-600 exhibiting the largest specific surface area at 21.29 m². 2 The highest specific surface area was 9.39 m² / g, indicating greater adsorption potential. This was followed by OS-400 and OS-800, with specific surface areas of 9.39 m² / g and 9.39 m² / g, respectively. 2 / g and 9.13m 2 / g, and finally 0.89m of OS-200. 2 / g, and the specific surface area of OS-y (0.59m²) 2 The difference is not significant ( / g).
[0050] Table 1. Statistical table of specific surface area between original oil shale samples and semi-coke materials from oil shale.
[0051]
[0052]
[0053] like Figure 4 As shown in the figure, FTIR analysis reveals the infrared spectra of oil shale before and after semi-coking. The surface functional groups of the oil shale remain largely the same before and after semi-coking, but the transmittance corresponding to different peaks changes, indicating a change in the activity of these surface functional groups. Semi-coking of oil shale did not alter its inherent functional groups, but it enhanced the activity of -OH, C=O, and Si-O-Si chemical bonds, specifically at 3445 cm⁻¹. -1 The nearby -OH stretching vibration peak, 1636 cm⁻¹ -1 The nearby C=O stretching vibration peak and 1082 cm⁻¹ -1 The intensity of the Si-O-Si antisymmetric stretching vibration peak in the vicinity is significantly enhanced.
[0054] Adsorption tests were conducted on the original oil shale sample (OS-y) and oil shale semi-coke materials (OS-200, OS-400, OS-600, OS-800) prepared at different roasting temperatures to observe the differences in their adsorption performance and determine the oil shale semi-coke material with the best adsorption effect.
[0055] The adsorption experiment mainly includes the preparation of the test solution (mother liquor), the preparation of heavy metal solutions of different concentrations, adsorption kinetics experiment, isothermal adsorption experiment, data statistical analysis, and experimental conclusions.
[0056] The technical approach and operational procedures of this experiment include:
[0057] Preparation of test solution (stock solution): Using analytical grade CdCl2·2.5H2O as the cadmium source, weigh 2.0316 g of cadmium chloride hemipentahydrate with a relative molecular mass of 228.36. Using lead chloride as the lead source, weigh 1.3422 g of lead chloride with a relative molecular mass of 278.11. Dissolve each in a 500 mL beaker, stir and shake repeatedly, and then standardize in a 1 L volumetric flask to obtain a 1000 mg / L standard solution.
[0058] Preparation of test solutions (stock solutions): Since the heavy metal content requirements of the solutions used for adsorption tests are relatively high, in order to improve the sensitivity and accuracy of heavy metal chemical speciation analysis data, analytical grade CdCl2·2.5H2O is used as the cadmium source and PbCl2 is used as the lead source to prepare standard solutions. According to different adsorption test contents and requirements, heavy metal solutions of different concentrations are prepared and corrected by standard solutions.
[0059] To prepare heavy metal solutions of different concentrations: Extract 200, 150, 100, 50, and 20 mL of 1000 mg / L cadmium solution using a pipette, and transfer each solution into a 1 L volumetric flask. Rinse the pipette three times with deionized water, then add deionized water and titrate to 1000 mL to obtain the desired cadmium solutions of different concentrations.
[0060] Extract 500, 300, 150, 100, and 50 mL of 1000 mg / L lead solution using a pipette, and transfer each solution into a 1 L volumetric flask. Rinse the pipette three times with deionized water, then add deionized water and titrate to 1000 mL to obtain lead solutions of different concentrations.
[0061] The adsorption kinetics experiment was divided into two parts: cadmium adsorption kinetics experiment and lead adsorption kinetics experiment. The materials involved were the passivation materials prepared in the previous stage, a total of 5, all of which were oil shale materials.
[0062] Table 2 Passivation materials used in adsorption kinetics experiments
[0063]
[0064] Cadmium adsorption kinetics test: Weigh 0.1g of the test material into an Erlenmeyer flask, and use a pipette to transfer 50mL of 100mg / L cadmium solution into a 100mL Erlenmeyer flask. Each test material is tested in triplicate. The mixture is shaken at 200r / min for 10min, 30min, 1h, 2h, 4h, and 8h. After filtration, the cadmium concentration in the supernatant is measured.
[0065] Lead adsorption kinetics test: Weigh 0.1g of the test material into an Erlenmeyer flask, and use a pipette to transfer 50mL of 300mg / L lead solution into a 100mL Erlenmeyer flask. Each test material is tested in triplicate. The solution is shaken at 200r / min for 10min, 30min, 1h, 2h, 4h and 8h. After filtration, the lead concentration in the supernatant is measured.
[0066] Oil shale materials prepared at different semi-coke temperatures affect Cd 2+ Pb 2+ The effect of adsorption:
[0067] like Figure 5 As shown, under the same experimental conditions, different half-joule OS affect Cd 2+ Pb 2+ The adsorption capacity and removal rate of OS showed significant changes. A coking temperature of 200℃ could activate OS to remove Cd. 2+ Pb 2+ Adsorption capacity for Cd 2+The adsorption capacity increased by 0.88 mg / g, a 20.15% increase, and the removal rate increased by 2.17%, a 25.27% increase. (Regarding Pb) 2+ The adsorption capacity increased by 8.67%, and the removal rate increased by 3.98%, but the adsorption capacity of OS-400 decreased. Compared with OS, its adsorption capacity for Cd decreased. 2+ The adsorption capacity decreased by 2.84 mg / L, and the removal rate decreased by 5.55%. (Regarding Pb) 2+ The adsorption capacity decreased less, still higher than the original adsorption capacity, but decreased by 6.54% compared to OS-200, and the removal rate decreased by 8.83%.
[0068] OS-600 exhibits a significantly increased adsorption capacity for Cd compared to OS. 2+ Pb 2+ The adsorption capacities increased by 2.33 mg / g and 14.79 mg / g, respectively, representing increases of 53.32% and 71.68%, and the removal rates increased by 50.04% and 68.45%, respectively. Compared to OS-200, the adsorption capacities increased by 1.45 mg / g and 13.00 mg / g, respectively, representing increases of 27.61% and 57.99%, and the removal rates increased by 19.77% and 62.00%, respectively. At OS-800, the adsorption capacity for Cd... 2+ Pb 2+ The adsorption capacity was only 43.11% and 37.23% of that of OS-600, and the removal rate was 43.21% and 39.97% of that of OS-600. Compared with the original sample, the adsorption capacity decreased by 1.48 mg / g and 7.45 mg / g, respectively.
[0069] Overall, as the coking temperature gradually increases, the effect of OS on Cd... 2+ Pb 2+ The adsorption capacity of Pb exhibits a fluctuating increasing trend, reaching its maximum at 600℃, and is particularly effective against Pb. 2+ It exhibits better adsorption performance, with an increased specific surface area, which stimulates the activity of the original -OH, C=O and Si-O-Si chemical bonds.
[0070] Effects of different adsorption times on Cd in oil shale semi-coke materials 2+ Pb 2+ The effect of adsorption:
[0071] At a dosage of 0.1g, pH=7, Cd 2+ Under the conditions of initial mass concentration of 100 mg / L and 25℃, the adsorption of Cd by semi-tar shale at different adsorption times 2+ Pb 2+ The adsorption capacity of OS for Cd is shown in the figure below. 2+ Pb 2+The adsorption process can be divided into three stages: rapid adsorption, fluctuating adsorption, and dynamic equilibrium.
[0072] like Figure 6 As shown, within 0–10 min, the addition of semi-coke OS reduced the Cd concentration in the solution. 2+ Pb 2+ The rapid decline is likely due to the large number of adsorption sites on the OS surface during the initial adsorption phase, resulting in high adsorption mass transfer kinetics and a strong attraction for Cd. 2+ Pb 2+ Rapid adsorption. Within 10–30 min, as adsorption time increased, different OS values showed varying effects on Cd. 2+ Pb 2+ The adsorption capacity began to change. The adsorption capacity of OS-200 and OS-600 continued to increase. OS-200 reached its maximum adsorption value of 5.24 mg / g at 30 min. The adsorption capacity of the others decreased, which means that after rapid adsorption, they entered a fluctuating absorption stage. At this time, the adsorption sites on the OS surface were gradually occupied and thus reduced, and the adsorption situation was not yet completely stable.
[0073] Within the range of 30 min to 240 min, the differences in adsorption capacity among different semi-tar shales further widened, especially within the range of 60 min to 240 min, where the adsorption capacity of each OS on Cd increased significantly. 2+ Pb 2+ The adsorption of Cd on the OS surface tends to reach equilibrium, indicating that adsorption has reached saturation. This process indirectly reflects the adsorption of Cd on the OS surface. 2+ Pb 2+ It diffuses into the OS and forms a complex. (This is related to Cd.) 2+ The adsorption behavior differed; at 60 min, OS-600 showed better adsorption of Pb. 2+ The adsorption amount fluctuated, while in Cd 2+ The solution rises gradually at this point.
[0074] Overall, the adsorption stabilization time was around 2 hours, and after 2 hours, all adsorption amounts entered a relatively stable range. Among them, OS-600 showed the best adsorption capacity for Cd. 2+ The adsorption capacity was between 5.98 and 6.69 mg / g for Pb. 2+ The adsorption capacity ranges from 31.66 to 35.42 mg / g.
[0075] The adsorption isotherm test was divided into two parts: cadmium adsorption isotherm test and lead adsorption isotherm test. The materials involved were the passivation materials prepared in the previous stage, a total of 2, both of which were oil shale materials.
[0076] Table 3 Passivating materials used in the adsorption isotherm test.
[0077]
[0078] Cadmium adsorption isotherm test: Weigh 0.1g of the test material into an Erlenmeyer flask, and use a pipette to transfer 50mL of cadmium solutions of 20, 50, 100, 150 and 200mg / L into a 100mL Erlenmeyer flask. Each solution of different concentrations is repeated three times. Shake at 200r / min in a horizontal shaker at 25℃ for 2h. After filtration, the cadmium concentration in the supernatant is measured.
[0079] Lead adsorption isotherm test: Weigh 0.1g of the test material into an Erlenmeyer flask, and use a pipette to transfer 50mL of lead solutions of 50, 100, 150, 300 and 500mg / L into a 100mL Erlenmeyer flask respectively. Each solution of different concentrations is repeated three times. Shake at 200r / min in a horizontal shaker at 25℃ for 2h. After filtration, measure the lead concentration in the supernatant.
[0080] Data statistical analysis: The experimental results were comprehensively analyzed to determine the optimal roasting temperature, stable adsorption time, and applicable concentration of oil shale semi-coke material.
[0081] Different Cd 2+ Effect of initial concentration on the adsorption performance of oil shale semi-coke materials:
[0082] like Figure 7 As shown in the figure, the original oil shale sample and OS-600 semi-coking oil shale with good adsorption performance were selected as adsorbents. Under the conditions of pH=7, dosage of 0.1g, adsorption time of 2h, and adsorption temperature of 25℃, the following figure shows that with the increase of Cd... 2+ As the concentration of Cd gradually increased from 20 mg / L to 100 mg / L, both OS-Y and OS-600 exhibited a consistent increase in adsorption capacity, while the removal rate decreased simultaneously. 2+ When the concentration exceeds 100 mg / L, the rate of decrease in adsorption rate of OS-Y and OS-600 is significantly reduced, and Cd 2+ Although the adsorption capacity is still increasing, the rate of increase has significantly decreased, especially...
[0083] OS-600 at 100 mg / L and 150 mg / L (Cd) 2+ The change in adsorption amount in the concentration solution was not significant, thus indicating that in Cd 2+ OS-600 exhibits better adsorption performance at concentrations below 100 mg / L, but its adsorption effect on Cd decreases above 100 mg / L. 2+ The increase in adsorption capacity was not significant. Overall, the adsorption capacity increased in the range of 50–200 mg / L Cd. 2+Within the concentration range, the adsorption capacity of OS-Y was between 0.92 and 4.93 mg / g, and the removal rate was between 4.80 and 8.46%. The adsorption capacity of OS-600 was between 3.43 and 8.42 mg / g, and the removal rate was between 8.20 and 31.54%. The adsorption capacity and removal rate were significantly improved after semi-coking modification at 600℃.
[0084] Different Pb 2+ Effect of initial concentration on the adsorption performance of oil shale semi-coke materials:
[0085] like Figure 8 It can be seen that OS-Y and OS-600 affect Pb 2+ The changes in adsorption amount and removal rate with Cd 2+ They are roughly similar, but the variations are not consistent, especially in Pb. 2+ When the concentration exceeds 100 mg / L, the increase in OS-Y adsorption decreases rapidly; at 150 mg / L, the adsorption amount increases by only 1.08 mg / g, while the removal rate remains essentially unchanged. (Regarding Pb...) 2+ When the concentration exceeds 300 mg / L, the increase in adsorption capacity and the decrease in removal rate further shrink. However, the increase in adsorption capacity of OS-600 is only observed in Pb in solution. 2+ A significant narrowing occurred at concentrations exceeding 300 mg / L, therefore, OS-600 was determined to have a Pb content of [missing information]. 2+ At concentrations below 300 mg / L, it exhibits better adsorption performance. Overall, at Pb concentrations of 50–500 mg / L... 2+ Within the concentration range, the adsorption capacity of OS-Y was between 13.74 and 23.88 mg / g, with a removal rate between 9.92% and 61.54%. The adsorption capacity of OS-600 was between 20.43 and 43.53 mg / g, with a removal rate between 19.09% and 91.55%. Compared to Cd... 2+ Solution, at lower Pb 2+ OS-600 can achieve a higher removal rate in concentrated solutions.
[0086] Oil shale semi-coke exhibits enhanced adsorption capacity for heavy metals cadmium and lead, but its mineralogical properties remain unchanged. The oil shale semi-coke material (OS-600) prepared at 600℃ shows improved adsorption capacity for Cd. 2+ Pb 2+ The adsorption effect is best at this material, as its increased specific surface area stimulates the activity of existing C=O chemical bonds. The adsorption performance stabilizes after 2 hours. This oil shale semi-coke material exhibits advantages of high efficiency, rapid adsorption, and stability in the adsorption of cadmium and lead ions from wastewater. It is particularly effective for Cd. 2+ Content <100mg / L or Pb 2+ For wastewater with a concentration of less than 300 mg / L, the adsorption effect of this oil shale semi-coke material (OS-600) is particularly significant.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a novel material for adsorbing heavy metals such as cadmium and lead, characterized in that, The method includes: The low-grade oil shale was ground through a 200-mesh sieve and dried to a constant weight. The dried oil shale is placed in a tubular rotary furnace, nitrogen is introduced and air is expelled, and the pressure inside the furnace is maintained at 0.2 atmospheres. Heated to 200℃-800℃ at a constant heating rate and calcined at this temperature for 2 hours; The calcined oil shale was cooled to room temperature, then ground and sieved again to obtain a new type of adsorbent material.
2. The method for preparing a novel material for adsorbing heavy metals cadmium and lead according to claim 1, characterized in that, The drying temperature of the low-grade oil shale is 45℃-55℃.
3. The method for preparing a novel material for adsorbing heavy metals cadmium and lead according to claim 2, characterized in that, The drying temperature of the low-grade oil shale is 50℃.
4. The method for preparing a novel material for adsorbing heavy metals cadmium and lead according to claim 1, characterized in that, The heating rate is 3-7℃ / min.
5. A method for preparing a novel material for adsorbing heavy metals cadmium and lead according to claim 4, characterized in that, The heating rate is 5°C / min.
6. A method for preparing a novel material for adsorbing heavy metals cadmium and lead according to any one of claims 1-4, characterized in that, The heating temperature is 600℃.
7. A novel material prepared by any one of the preparation methods described in claims 1-6, characterized in that, Its effect on Cd in wastewater 2 The suitable adsorption concentration for Pb is <100 mg / L. 2 The suitable adsorption concentration for + is <300mg / L.
8. The application of a novel material in the adsorption of cadmium and lead heavy metals in wastewater, characterized in that, The novel material is prepared by any one of the preparation methods described in claims 1-6.
Citation Information
Patent Citations
A method for preparing an oil shale semi-coke adsorbent
CN110523373B